Psoriasis comorbid with atherosclerosis meets in lipid metabolism - Liuping Chen; Huiqi Chen; Huiqi Chen; Sien Guo; Sien Guo; Zhijun Chen; Zhijun Chen; Haifeng Yang; Yanjiao Liu; Xiaoling Chen; Xinming Chen; Tingting Du; et al. (Frontiers Media S.A., 2023)
Psoriasis (PSO) is a common skin disease affecting approximately 1%-3% of the population, and the incidence rate is increasing yearly. PSO is associated with a dramatically increased risk of cardiovascular disease, the most common of which is atherosclerosis (AS). In the past, inflammation was considered to be the triggering factor of the two comorbidities, but in recent years, studies have found that lipid metabolism disorders increase the probability of atherosclerosis in patients with psoriasis. In this review, we discuss epidemiological studies, clinical treatment methods, risk factors, and lipid metabolism of psoriasis and atherosclerosis comorbidities.